Unequal Relations and Madagascar's Struggle for Sovereign Progress under Neo-Imperialism - Emynorane, Ralaivao Hanginiaina; Arrive, Jean Tsitaire; Bien-Aimé, Whega Danitsaike (Review of International Relations (Jurnal Kajian Ilmu Hubungan Internasional), 2025)
This study aims to examine how unequal relations shape Madagascar's struggle for sovereign progress within a contemporary neo-imperial context. Using a qualitative approach, the study draws on an extensive documentary corpus, discourse materials, and data from 15 semi-structured interviews conducted with national policymakers, representatives of international actors, and civil society leaders. The findings show that structural dependency, rooted in long-standing economic hierarchies and externally designed development pathways, continues to limit Madagascar's ability to set its own priorities. External influence is sustained through financial leverage, investment arrangements, diplomatic involvement, and normative frameworks that shape policy direction without requiring direct political control. Institutional vulnerabilities including administrative limitations, weak decentralization, and gaps in technical capacity further expose the country to external dominance, particularly in sectors tied to strategic resources and development financing. These intertwined dynamics reveal a persistent gap between formal independence and effective sovereignty, visible in the formulation, negotiation, and justification of national policies. Strengthening sovereign progress therefore depends on enhancing institutional capacity, improving negotiation mechanisms, ensuring transparency in external engagements, and promoting governance practices that reflect domestic rather than external interests.